The population biology of Acanthocephalus clavula in European Eel Anguilla anguilla L., brown trout Salmo trutta L. and Asellus meridianus Rac., with special reference to the suitability of brown trout as a definitive host - Dooley, Emma Jane (Trinity College (Dublin, Ireland). Department of Zoology, 2010)
Acanthocephalus clavula is an acanthocephalan parasite of freshwater fishes which is distributed across Ireland, Great Britain and continental Europe. In Ireland, the intemiediate host of A. clavula is the isopod Asellus meridianus. The preferred definitive host of A. clavula across its distribution is the European eel Anguilla anguilla. A. clavula has been recorded in brown trout Salmo trutta in Ireland on several occasions, however in other locations the occurrence of this host-parasite combination is rare.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin